Marvell's Aviary: The Cassowary. Issue 2 (11th October 2018) - von Maltzahn, Nicholas
Abstract : Marvell's shrewd references to birds in his poetry and prose come in 'Last Instructions' to include that most exotic of fowl, the cassowary. By way of simile the voracious cassowary there serves to comment on the voracious Excise tax. Editors have overlooked how near to hand cassowaries might be for Marvell, who seems to have enjoyed them among the sights of St James's Park, where the royal aviary was being newly improved in the 1660s and included such tribute from the East India Company. In the cassowary Marvell had met with a wonder that plainly caught his eye, leaving him with a lasting metaphor for courtly excess and for the all-devouring Excise to which that might lead.